Statistical Testing using Automated Randomization - Designing and implementing a system for generation of exploratory test cases for an automated testing environment. - Sternerson, Jonas; Firoozfam, Mahsa (My University, 2010)
The cost of software system testing constitutes a large portion of the total software development cost in most projects. High-quality testing requires a well structured approach, thorough planning and experience in the field. The human resource cost is often high if a large development project will often employ more testers than developers. Many consider good testing to be both an art and a science, and in this view it is not possible to replace an experienced tester by an automatic testing tool.[11] There are at the same time also many areas in testing that are highly repetitive, such as the repeated execution of a test that has been designed by a tester. By handling the less advanced testing tasks, good testing tools can save time for the tester and both lower the testing cost of the development project and increase the quality of the developed product. One main goal of testing tool research and development is to increase the automation of the parts of testing where a scientific method can be applied, and leave the tester free to focus more on those parts that are still considered art. This master's thesis will present the design and implementation of a system addition to an existing automatic testing tool that will enable the tool to perform more types of software testing automatically.
Keywords: Programvaruteknik; Software Engineering